Shakespeare a life - Honan, Park (Oxford; New York Oxford University Press, 1998)
A very complete, accurate and up-to-date account of Shakespeare's life, drawing on a range of new material. Explores Shakespeare's attitudes to women through his relationships with Anne Hathaway and his own daughters.
Includes bibliographical references (p. 425-450) and index.
Keywords: Shakespeare, William, 1564-1616 -- Biography; Dramatists, English -- Early modern, 1500-1700 -- Biography